تكامل المسؤولية الفردية والجماعية في بناء أخلاق المجتمع من خلال تفسير سورة البقرة /‏ - أحمد،جمال الأحمد (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This research aims to disclose the significance of integration of individual as well as communal duties in building ethics of society through the interpretation of Surah al-Baqarah; to reveal its significant impact on instructing the moral values of society and setting on its members high conduct and best comportment. In addition, the study investigates how this integration can be achieved and how the need for adhering to Qur'anic principles can ensure the success of this integration and make it balanced so as to determine the duty of each individual according to them potentials, and characteristics they have to fulfil to achieve the desired goal-the integration of individual and communal duties in building the moral values of society. In view of this, the study adopted two approaches. First, the inductive approach in order to track down and collect the views of the commentators and scholars who dealt with the criteria and principles of individual and communal duties in inculcating the moral values of society through the interpretation of Surah al-Baqarah. Second, the analytical approach served to analyze the views of the commentators and scholars that have pointed out to the necessity of integration of individual and communal actions in instructing the moral values of society. Hence, this study is set to crystalize the significance of integration of individual as well as communal duties in instilling moral values of society, to discover the principles and criteria that can ensure the integration of this task, and to know what are the means and methods suitable for this purpose. In addition, the study has addressed the obstacles facing both individual and communal actions and concluded by mentioning the outcomes resulting from the integration process of individual and communal duties in inculcating the moral values of society.